PENGARUH KETERBATASAN MODAL, PRODUK, HARGA, TEMPAT, DAN PROMOSI TERHADAP KEBERHASILAN UMKM ACEH UTARA (Studi Kecamatan Tanah Jambo Aye dan Kecamatan Baktiya) - Hayati, Ismatul; Simahatie, Mai (IndOmera, 2025)
The contribution of MSMEs to GRDP in the region is very significant, such as in Aceh province which reached 55.56 percent in 2024. The independence of MSMEs and their success need to be maintained, by finding solutions to supporting factors and becoming challenges in the future. Such as limited business development capital, technology needed for work efficiency, saving distribution and promotion costs, and most importantly improving the quality of production. This was done by micro research on MSMEs in Jambo Aye and Baktiya sub-districts, where there are quite a lot of MSME units in the area. For this reason, an associative method with a quantitative approach was applied. And using a multiple regression analysis model. The results of the analysis show, (1) there is a significant influence of business capital, product, price, distribution location, promotion factors on the success of MSMEs. 2) The results of the regression analysis are expressed in a significant model: Y = 3.362 + 0.575 X1 + 0.608 X2 + 0.685 X3 + 0.625 X4 + 0.501 X5. Of the five factors investigated, price was found to have the largest contribution, followed by the distribution location factor.